PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PRAMA SANUR BEACH HOTEL BALI - Kadek Januarsa Adi Sudharma; Dheanatul Islamiyyah (Humano: Jurnal Penelitian, 2022)
Employees, employees, workers are human beings who use their energy and abilities to get a reward in the form of money or in other forms to the company. The success of a company is inseparable from the role of employees, because employees are not just an object, they can be said to be planners, controllers and assets of a company by contributing to the company in the form of their abilities, expertise and skills. Therefore, job satisfaction and employee motivation are very influential for a company. This study aims to determine how the influence of job satisfaction and work motivation on employee performance at Prama Sanur Beach Hotel Bali. This study used a qualitative method, in which researchers used data collection techniques through in-depth interviews and participant observation. The results show that the effect of job satisfaction and work motivation on employee performance is very influential, the company is currently still unable to provide maximum job satisfaction to employees because work wages are still cut due to Covid-19, therefore work motivation cannot be measured with certainty. , because employees still want to get better to improve their performance.